Dasar-dasar psikologi kualitatif : Pedoman praktis metode penelitian / Jonathan A. Smith; Penerjemah, M. Khozim; Editor, Romdoni - SMITH, Jonathan A.; KHOZIM, M.; ROMDONI (Nusa Media, 2013)
viii, 348 hlm. ; 23,5 cm